Occurrence and Concentration of Heavy Metals in a Rural Spring in South-eastern Nigeria - ED Anyanwu; OG Onyele (Journal of Applied Sciences and Environmental Management, 2018)
Water is essential for life on earth and its quality is important for health and economic development; seasons, anthropogenic influences and natural processes affect the chemical composition of water. Springs are natural outflow of water from an underground supply to the ground surface and the quality may be altered due to exposure to metallic elements. Some of these elements are essential for humans; they can be dangerous at relatively high exposure levels. The aim of this study was to assess the occurrence and concentrations of heavy metals in a rural spring and determine its suitability for human consumption. Eight (8) heavy metals (Mn, Cu, Pb, Fe, Zn, Cd, Cr and Ni) were assessed between January and June 2017 in 3 stations; using Atomic Absorption spectrometer (AAS) and compared with SON and WHO standards. pH and Electrical conductivity were also determined in association with the metals with hand-held meters. Manganese, chromium, lead, iron and cadmium exceeded acceptable limits in various percentages of the samples and could basically be attributed to geogenic source exacerbated by seasonal and anthropogenic influences. The values of lead, iron and cadmium were higher and pose serious health risk to the consumers of the spring water over time. Rural springs hitherto considered safe due to little or no anthropogenic influences have been found to be unsafe due to geogenic contamination. The spring is therefore not suitable for drinking but can used for other domestic purposes. Human health risk assessment is recommended for this spring.